The influence of patients' complexity and general practitioners' characteristics on referrals to outpatient health services in an Italian region - Francesca Valent; Laura Deroma; Antonella Franzo; Michele Gobbato; Giorgio Simon; Luigi Canciani; Loris Zanier (Istituto Superiore di Sanità, 2015)
BACKGROUND. Patient referrals to outpatient health services may affect both health outcomes and health expenditures. General practitioners (GP) have a crucial role in driving the use of outpatient services and recognizing factors which affect referrals is important for health managers and planners. OBJECTIVES. We investigated patient- and physician-related determinants of patient referrals in an Italian region. METHODS. This was cross-sectional study based on the individual linkage of administrative databases from the health information system of the Friuli Venezia Giulia region. For each GP of the region, the association of the number of patient referrals to different types of outpatient services with the proportion of patients with chronic conditions, with the number of hospital admissions and drug prescriptions in 2012, and with GP's characteristics was investigated through multilevel multivariable Poisson regression models. RESULTS. Some chronic conditions (e.g., cancer, autoimmune diseases, endocrine diseases, digestive system diseases) were positively associated with the number of referrals, as were hospital admissions and drug prescriptions. Time since GP's graduation was inversely related with referrals. CONCLUSION. Patient complexity and GP's experience affect referral rates. These factors should be considered in case of a reorganization of the general practice structure in Friuli Venezia Giulia.